Relative performance of different strategies for wave attenuation by periodic structures - McMahon, Darryl (2017)
For a periodic structure of symmetric scatterers, such as a ribbed plate or cylinder, Bloch-Floquet waves (BFW) are well-known periodic structure waves (PSW). Conventional wisdom is to attenuate BFW propagation by re-flections, energy absorption or stopping bands. Recent theoretical results show that periodic structures with asymmetric scatterers do not lead to BFW, revealing more possibilities for noise reduction through these dif-ferent PSW. This paper compares the performance of reciprocal and nonreciprocal wave propagation as meth-ods for PSW attenuation. It is found that nonreciprocal wave propagation, such as could be realized with asymmetric metamaterial scatterers, could achieve significantly better attenuation with relatively small deviations from symmetric scatterer properties.